SOLID WASTE GENERATION, PLANNING, AND PROJECTION IN WA, GHANA - Owusu-Sekyere, E.; Amoah, S. T.; Wedam, E. A. (UDS International Journal of Development, 2017)
The search for cutting-edge policy intervention for sustainable solid waste management (SWM) continues to generate thoughts, interest and research in Ghana. This is evidenced from the speed, scale, scope and complexity of countless government efforts at exploring innovative actions aimed at achieving perfectly formed SWM strategies. Nonetheless, the efforts are being hampered by limited forecast data regarded as the backbone for proper SWM planning. The objective of this article was to forecast the quantity of annual solid generation in Wa between 2016 and 2026. The study adopted the Autoregressive Integrated Moving Average model in estimating the predictions. The results indicate that without structural interruptions of the current solid waste generation trends, by 2026, the quantity of solid waste that will be generated in Wa may be six times more than that of 2016. Given the fact that the negative externalities of poor SWM are increasingly reaching crisis point and that existing protocols are unable to ameliorate the problem, we suggest a shift in paradigm if Wa is to be counted among the league of world class filth-free cities in the near future. Keywords: Autoregressive Moving Average, Forecast, Urbanization, Solid waste, WaÂ 